INFLUÊNCIA DE COBERTURAS DE INVERNO E ÉPOCAS DE COLHEITA NA SANIDADE DOS GRÃOS DE MILHO - Manfron, Felipe (2016)
Bearing in mind the importance of the grains health in the cultivation of corn, as well as the greater susceptibility of modern hybrids to grain pathogens that cause quantitative and qualitative damage and the possible production of mycotoxins, this study evaluated the influence of different winter cover, such as canola, turnip, black oat, pea, wheat, vetch, consortium (black oat, turnips and vetch), and fallow on grain quality. In addition, two corn hybrids and three harvest dates, one of which was close to physiological maturity, followed by two other harvests 15 days apart, were also evaluated. The objective of this research was to evaluate the influence of these parameters on the occurrence of damaged kernels and the incidence of fungi in corn kernels. The experiment was conducted in Piraí do Sul, PR, Brazil, which is in a Cfb climate zone, during the harvests of 13-14 and 14-15 using the commercial hybrids P30F53YH and P30R50YH. The following were evaluated: the population of plants per hectare; the severity of leaf diseases; the incidence of stalk rot; thousand grain weight and yield. The incidence of rotten grains and fungi in the grains was determined by using the blotter test method in the laboratory. For all the foliar diseases that were evaluated, the AUDPC was higher in the second harvest (2014-2015). In the two harvests the percentage of stalk rot was highest in fallow, followed by peas. In the 13-14 harvest there was a higher incidence of rotten kernels in the third phase of the harvest. There was a higher incidence of rotten kernels in the combined analysis of the harvest in 14-15 compared with the previous harvest. The blotter test showed a higher incidence of Fusarium sp., Aspergillus sp., Cladosporium sp. and Rhizopus sp., in the first two harvests but the incidence of Penicillium sp. increased during the harvests. The highest values of incidence of Fusarium sp. were observed in the covers of wheat, canola, oats and vetch in the 13-14 harvest, differing only in terms of fallow. In the 14-15 harvest the highest incidence of Fusarium sp. was in relation to the covers of canola, wheat, vetch and consortium. Significant interaction between the harvest time and the preceding crop was observed and the highest values were for the second phase of the harvest in relation to the covers of peas, wheat and vetch. The incidence of Aspergillus sp. in the 14-15 harvest was statistically higher for fallow, which differed from the others. The lowest incidence of Aspergillus sp. was found in the covers of oats and canola, differing from vetch and field peas. Significant interaction was observed in relation to the time of harvest and the hybrid. The highest incidence of Aspergillus sp. in the 13-14 harvest was for the P30F53YH hybrid in the first phase of the harvest. In the 14-15 harvest the highest incidence of Aspergillus sp. was observed for the P30R50YH hybrid during the first phase of the harvest. A significant interaction was also observed between preceding crops and the hybrids in relation to the incidence of Aspergillus sp. This was especially true of fallow with the P30F53YH hybrid in the 13-14 harvest and the P30R50YH hybrid in the 14-15 harvest. Significant interaction was observed between the times of harvest and preceding crops in relation to the incidence of Aspergillus sp. and this was especially true of fallow in the first phase of the 14-15 harvest. Significant interaction was observed between the times of harvest, preceding crops and the hybrids regarding the incidence of Aspergillus sp. This was especially true in relation to the P30F53YH hybrid on fallow in the first phase of the 13-14 harvest, and the P30R50YH hybrid on fallow in the first phase of the 14-15 harvest. Regarding the incidence of Cladosporium sp. and Rhizopus sp., different behavior was observed with respect to coverage. The incidences of all the grain fungi were higher in the second harvest (2014-2015). There was higher productivity and thousand grain weight, relative to the joint analysis, in the 13-14 harvest compared to the 14-15 harvest.